Cold Atmospheric Plasma: A Noteworthy Approach in Medical Science (Sciences of Pharmacy, 2023)
Cold atmospheric plasma (CAP) is a novel technology with boundless significance that can be used in the medical sector that offers noninvasive in-vivo applications without damaging the living tissues. CAPs can be obtained by curtailing the concentration of high-energetic electrons per phase and by freezing molecules/atoms (devoid of charge) in plasma utilizing gas circulation and atmospheric air, which includes a variety of charged and neutral reactive entities, UV rays, electric currents, and fields, etc. that have an influence on cellular material in a multitude of diverse manners. Reactive oxygen species (ROS) and reactive nitrogen species (RNS), produced by the plasma, essentially cause biological and therapeutically advantageous plasma effects. CAP plasma has several important biological functions, including the deactivation of pathogens, induction of tissue restoration and cell propagation, the annihilation of cells by triggering apoptosis, etc. Several fundamental concepts are defined, even if the precise process of the effect of plasma on biomolecules is still not properly identified. Depending on the biological synthesis of RNS and ROS in reactions to plasma emissions, the present review described several aspects of plasma therapy in neuroscience, particularly in anti-glioblastoma, neuro-differentiation, and neuroprotection and also the various applications of CAP in medical fields where it is used in the therapy of SARS-CoV-2, cancer therapy, and chronic and acute wounds. Furthermore, the proliferation in stem cells, dental medicines, dermatology, and a brief insight into CAP devices and their risk factors was highlighted.